Island formation of Er(trensal) single-ion magnets on graphene observed on the micrometer scale. Issue 16 (2nd March 2021) - Dreiser, Jan; Wäckerlin, Christian; Buzzi, Michele; Pedersen, Kasper S.; Bendix, Jesper
Abstract : The island formation of Er(trensal) single-ion molecular magnets on graphene/Ru(0001) has been studied using X-ray photoelectron emission microscopy. Abstract : We have studied the morphology of Er(trensal) single-ion molecular magnets adsorbed on graphene/Ru(0001) using X-ray photoemission electron microscopy (X-PEEM). By exploiting the elemental contrast at the erbium M5 edge we observe the formation of molecular islands of homogeneous height with a lateral size of several micrometers. The graphene/Ru(0001) substrate exhibits two different signal levels in bright-field low-energy electron microscopy (LEEM) and in X-PEEM, which are ascribed to the presence of small-angle rotational domains of the graphene lattice. We find that the Er(trensal) molecules form islands solely on the bright areas, while the remaining dark areas are empty. Our results are important for the growth and study of the molecule–inorganic hybrid approach in spintronics schemes.